Pigeon Pea [Cajanus cajan (L.) Millsp.] Seed Meal in Layer Diets: 3. Effect of Higher Inclusion Level and Prolonged Feeding of Raw or Processed Pigeon Pea Seed Meal Diets from Pullet Chick Stage on the Laying Performance of Pullets - Amaefule, K.U.; Oguike, M.A.; Ironkwe, M.O.; Obioha, F.C. (International Journal of Poultry Science, 2007)
Black Bovan Nera pullets at point of lay (19 weeks old) that were fed pigeon Pea Seed Meal (PSM) diets during the pullet chick and grower stages of life were used to determine the effect of higher inclusion level and prolonged feeding of raw or processed PSM diets from the pullet chick stage on the laying performance of pullets. Brown colored pigeon pea seeds were used as raw, boiled for 30 min, toasted for 30 min, or soaked in water for 24 h, all of which were milled to pass through a 2 mm sieve. Each diet had three replications; each replicate had eight birds in a Completely Randomized Design (CRD). Parameters measured were feed intake, live weight, hen-day production, age at 1st, 25 and 50% egg production, external and internal egg quality characteristics. Results showed that layers fed boiled PSM diet had significantly (P<0.05) higher hen-day production (67.04%), egg weight (57.63 g), shell weight (6.50 g) while those fed raw PSM diet had the lowest (55.07%) hen-day production. It was concluded that raw or processed pigeon Pea Seed Meal (PSM) could be included as 30% of the whole diet of layers that had received 10 and 20% PSM based diets during their pullet chick and grower stages of life, respectively. Boiled PSM diet would improve hen-day egg production, toasted PSM diet would increase feed intake of layers while PSM diets will have no regular effects on external and internal egg quality characteristics of eggs laid by layers fed PSM diets.